Analysis of environmental conditions in the Baixotes stream, in the lower Tietê river basin, in Birigui (São Paulo, Brazil) - Gonçalves, Stephanie Campos; Martins, Clélia Rosilene Bergo; Romero, Danielli Cristina Granado; Okimoto, Fernando Sérgio (National Journal of City Management, 2025)
Objective - To analyze the environmental conditions of sections of the Ribeirão Baixotes in Birigui/SP. Methodology - Application of a Rapid Assessment Protocol (RAP) in two distinct climatic periods: one during the dry season and the other during the regular rainy season of 2023 in the region. Originality/Relevance - The Rapid Assessment Protocol (RAP), despite being a consolidated methodology in the academic and scientific community, has been little explored. Its ease of use, low technological cost, and precision allow for robust environmental analyses. Results - The results showed anthropic alterations of varying degrees of intensity in the four sections analyzed in both sampling periods. The most impacted areas were those close to the urban zone and the section where the water intake point for the municipality’s supply is located. Subsequently, the assessment tool indicated several environmental changes in the section upstream from the intake. Finally, it is pointed out that the area after the effluent discharge from the Sewage Treatment Plant is in better environmental condition. The recorded results are alarming and require urgent interventions for recovery. Theoretical/Methodological Contributions - The study reflects the conditions of the Ribeirão Baixotes, but it also mirrors the vast majority, if not all, of urban water bodies. The analyses performed can be used by municipal and water management agencies. Social and Environmental Contributions - The methodology itself allows for an understanding of the important variables for maintaining or restoring the environment surrounding water bodies, promoting the awareness and consciousness necessary for proactive actions and positive environmental impacts.